CUSTOMER SATISFACTION TOWARDS THE RAIL SERVICES IN MALAYSIA AND THAILAND - Melan, Mustakim; Hassan, Mohamad Ghozali; Prapinit, Pichit; N, Radasa; B, Pachateeya (CENTRAL ASIA AND THE CAUCASUS, 2024)
Rail industry is most popular mode in land transport among the commuters for short and long distance movements in all countries. In 2018, rail industry transported about 37 million in Malaysia and Thailand approximately 35 million passengers in overall types of services. The demand expected to be increased from time to time and depending on the improvement in the services. One of the problems for future improvement is the quality of the services and their focus in enhancing on passengers’ requirements. The research discusses on the development of service quality of rail services and cross border in Malaysia and Thailand. It also investigates empirically towards customers’ satisfaction for rail industry and based on the present problems towards the services in the industry. This is a quantitative research with relevant literature with variables dimensions and using descriptive analysis to validate on the data obtained. The survey was conducted amongrail users using questionnaires among 300 respondents and based on their satisfaction on service quality, reliability, facilities and accessibility. This research uses the theory of Customer Satisfaction Index (CSI) to measure the level of satisfaction among respondents. This study was analyzed using Statistical Package for the Social Sciences (SPSS) and the results indicated that service quality, reliability, facilities and accessibility are playing the significant relationship towards customers’ satisfaction for rail services. It also suggests that the accepted variables are able to be used in future initiatives in developing the customers’ satisfaction in the operators of rail industry at both countries.